Pola Asuh Anak Cerdas Istimewa dalam Islam - Hery Setiyatna; Putri Melati (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This study aims to determine how Islamic parenting is applied to special intelligent and gifted children. A special intelligent child is a child who has intelligence above the average of his peers. They are children who have high independence, have self-taught behavior, cannot be detected by other people and can create ideas spontaneously. Special intelligent children have intelligence above 130 (Waschler scale), they have high-order thinking patterns and cannot be equated with their peers who only have normal intelligence. The pattern of education and parenting applied by parents to their children can use various methods that have been taught by the Prophet in Islamic religious teachings. These methods include modeling methods and noble ethics, situational and conditional methods, questioning methods, analogical methods, and dialogical interaction methods. This research was conducted to provide information about proper parenting in Islam through the methods taught by the Prophet.